1980
DOI: 10.1007/bf00636790
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of propranolol pharmacokinetics to antihypertensive effect and beta-adrenergic blockade in the treatment of hypertension

Abstract: The pharmacokinetics of propranolol in 16 hypertensive patients was compared after the first oral dose of 80 mg and during chronic treatment with 80 mg bd. The degree of beta-adrenergic blockade was estimated by the reduction in maximal exercise heart rate. No significant change in plasma half-life occurred and there was no correlation between the mean steady-state propranolol concentration and beta-adrenergic blockade or antihypertensive effect. A linear relationship was observed between the decrease in blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Many studies have demonstrated correlations between plasma (or blood) levels of propranolol and its pharmacological effect (Coltart & Shand, 1970;Pine et al, 1975;McAinsh et al, 1978;Mullane et al, 1982) but others could not establish this correlation (Krediet et al, 1980;Lehtonen et al, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated correlations between plasma (or blood) levels of propranolol and its pharmacological effect (Coltart & Shand, 1970;Pine et al, 1975;McAinsh et al, 1978;Mullane et al, 1982) but others could not establish this correlation (Krediet et al, 1980;Lehtonen et al, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…These investigators concluded that this was because the urinary propranolol concentrations might better reflect total exposure to propranolol over the day than plasma propranolol concentrations. As other authors have failed to find any relationship between the area under the plasma concentration-time curve or mean plasma propranolol concentrations over the day, this seems a somewhat simplistic explanation (Krediet et al 1980). In addition, although failing to find a relationship between plasma propranolol concentrations and antihypertensive effect, a good relationship was found between the extent of Pblockade and the antihypertensive effects of propranolol (Krediet, et al 1980) and it was considered that the antihypertensive effect parallels Pblockade.…”
Section: Does Long Acting Propranolol Maintain Blood Pressure Controlmentioning
confidence: 96%
“…As other authors have failed to find any relationship between the area under the plasma concentration-time curve or mean plasma propranolol concentrations over the day, this seems a somewhat simplistic explanation (Krediet et al 1980). In addition, although failing to find a relationship between plasma propranolol concentrations and antihypertensive effect, a good relationship was found between the extent of Pblockade and the antihypertensive effects of propranolol (Krediet, et al 1980) and it was considered that the antihypertensive effect parallels Pblockade. 60 Thus, in the absence of a clear concentrationeffect relationship it was reasonable to attempt once-daily conventional propranolol therapy for the treatment of hypertension.…”
Section: Does Long Acting Propranolol Maintain Blood Pressure Controlmentioning
confidence: 96%
“…This seems to be consistent with previous studies where even if a significant correlation between plasma levels of several f3-adrenoceptor blockers and fall in some of blood pressures was found, it was of a weak order or equivocal (Anavekar et al, 1975;Collste et al, 1976). Others did not find any correlation between antihypertensive response and plasma concentration of propranolol (Kredit et al, 1980;Lehtonen et al, 1977) or metoprolol (Bengtsson et al, 1975;von Bahr et al, 1976).…”
Section: Discussionmentioning
confidence: 97%